(untitled) (Journal of Parents and Teachers, 2014)
This article offers some suggestions and activities to work in the class playfully and participatively with some poems by Juan Ramón Jiménez, especially in the first years of secondary school. This article tells us about his life, his work, his time and what teachers want to get from students: mainly make them more familiar with this writer’s poetry and stimulation of imagination and creativity of students through poetry.